The Logical Pragmatics of Arguments in Argumentation (Journal of the College of Education for Women, 2022)
Logic is understood so far as a product perspective, either formal or informal. The topic is still, though interesting, imprecise, sketchy and problematic. Besides, the relevance of logic to linguistics has not been explained. This research focuses on dealing with logic as a product and a process. It introduces how logic is relevant to understanding language. Logic is surely not irrelevant to real human language. In this research, we coin 'logical pragmatics' to refer to "the structure of an argumentation and its parts used by the speaker for the purpose of persuasion to have an effect in the addressee and passive audience”. As such, the research mainly aims at providing a definition of "logical pragmatics" as well as developing an ideal model for it. To accomplish this aim, the research studies what this approach entails and the relevance of logic and pragmatically oriented contributions to the field of argument and argumentation. The study mainly concluded that in real communication, simple logical relations become very complex and part of a wider context where we have a speaker's communicative intention, a hearer's communicative inference, and context.